IMPROVING THE ECO-TOURISM EXPERIENCE WITH GUIDING SERVICES AND CHSE - Hary Hermawan (LPPM Universitas Bina Sarana Informatika, 2022)
ABSTRACTour guides are other people who most often interact with tourists while travelling in an ecotourism destination. Therefore, the service activities provided by the guide are considered entirely instrumental in shaping the tourist experience. In this Covid-19 pandemic condition, the implementation of the CHSE Health protocol is also considered very important in supporting the creation of a quality tourist experience. This article presents a discussion regarding the influence of CHSE guidance services and protocols on the tourist experience in the Nglanggeran Ancient Volcano Ecotourism Area. The method used is a quantitative inferential method using the Partial Least Square (PLS) approach. The results show that the guidance service has a positive effect on creating the tourist experience. However, the CHSE health protocol implementation has not been proven to affect the tourist experience.Keyword: Tourist experience, tour guide service, chse, new normal ABSTRAKPemandu wisata adalah orang lain yang paling sering berinteraksi dengan wisatawan selama berwisata di suatu destinasi ekowisata. Oleh karena itu, kegiatan pelayanan yang diberikan oleh pemandu dianggap sepenuhnya berperan dalam membentuk pengalaman wisatawan. Dalam kondisi pandemi Covid-19 penerapan protokol kesehatan CHSE juga dinilai sangat penting dalam mendukung terciptanya pengalaman wisata yang berkualitas. Artikel ini menyajikan pembahasan mengenai pengaruh layanan pemandu wisata dan protokol kesehatan CHSE terhadap pengalaman wisatawan di Kawasan Ekowisata Gunung Api Purba Nglanggeran. Metode yang digunakan adalah metode kuantitatif inferensial dengan menggunakan pendekatan Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa layanan pemandu wisata berpengaruh positif dalam menciptakan pengalaman wisatawan. Namun, penerapan protokol kesehatan CHSE belum terbukti mempengaruhi pengalaman wisatawan.Kata Kunci: Pengalaman wisatawan, pelayanan pemandu wisata, CHSE, new normal